Clinical and Genetic Spectrum of Stargardt Disease in Argentinean Patients - Mena, Marcela D.; Moresco, Angélica A.; Vidal, Sofía H.; Aguilar-Cortes, Diana; Obregon, María G.; Fandiño, Adriana C.; Sendoya, Juan M.; Llera, Andrea S.; Podhajcer, Osvaldo L. (Frontiers in Genetics, 2021)
Purpose To describe the clinical and molecular spectrum of Stargardt disease (STGD) in a cohort of Argentinean patients. Methods This retrospective study included 132 subjects comprising 95 probands clinically diagnosed with STGD and relatives from 16 of them. Targeted next-generation sequencing of the coding and splicing regions of ABCA4 and other phenocopying genes (ELOVL4, PROM1, and CNGB3) was performed in 97 STGD patients. Results We found two or more disease-causing variants in the ABCA4 gene in 69/95 (73%) probands, a single ABCA4 variant in 9/95 (9.5%) probands, and no ABCA4 variants in 17/95 (18%) probands. The final analysis identified 173 variants in ABCA4. Seventy-nine ABCA4 variants were unique, of which nine were novel. No significant findings were seen in the other evaluated genes. Conclusion This study describes the phenotypic and genetic features of STGD1 in an Argentinean cohort. The mutations p.(Gly1961Glu) and p.(Arg1129Leu) were the most frequent, representing almost 20% of the mutated alleles. We also expanded the ABCA4 mutational spectrum with nine novel disease-causing variants, of which eight might be associated with South American natives.